1976
DOI: 10.1007/bf02371633
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life history and respiratory activity of “wild” and colonized Caribbean fruit flies [Dipt.: Tephritidae]

Abstract: Insects that are colonized for use in biological control programs must be behaviorally functional with respect to target field populations. To quantify adaptation during colonization and identify some of the behavioral changes that occur during the process, comparable colonies of field-collected and laboratoryadapted Caribbean fruit flies, Anastrepha suspensa (LoEw), were monitored through 5 generations for fertility of eggs, weights and yields of pupae, and viability, sex ratio, insemination frequency, fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…recovery cycle", although well known to the insect rearing practioner, rarely has been quantified. However, Leppla et al (1976) found that after 35 generations a caribbean fruit fly colony, transferred from routine to experimental rearing protocols, underwent nearly as much adaptation as newly introduced wild populations. Both lines had just 43% mated 9 9 after 5 generations of isolated rearing but only the wild had a prolonged preoviposition period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recovery cycle", although well known to the insect rearing practioner, rarely has been quantified. However, Leppla et al (1976) found that after 35 generations a caribbean fruit fly colony, transferred from routine to experimental rearing protocols, underwent nearly as much adaptation as newly introduced wild populations. Both lines had just 43% mated 9 9 after 5 generations of isolated rearing but only the wild had a prolonged preoviposition period.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Mitchell et al (I965) determined that the Oriental fruit fly, Dacus dorsails Hendel, becomes more lab-adapted with each passing generation until the tenth. The Caribbean fruit fly, Anastrepha suspensa Loew, was similar; its oviposition rate increasing from < 5 to 43% of the level of the established lab colony by the 5th generation (Leppla et al, 1976). With the Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann), it required more than 5 generations to "get the culture going", so R6ssler (1975a) measured differences between wild and tab strains at 8 and ca.…”
mentioning
confidence: 99%
“…There are reports of delays in the commencement of oviposition in newly-established colonies relative to long-established colonies, but it is not clear to what extent this is due to reduced readiness to lay per se, rather than to a delay in the onset of oviposition resulting from delayed mating (e.g. HIGHTOWER et al 1972;LEPPLA et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…HIGHTOWER et al 1972;RAULSTON 1975;LEPPLA et al 1 976). Improvement in egg production in successive generations after colonization have also been documented (LEPPLA et al 1976(LEPPLA et al , 1983. In addition, a number of instances have been reported of relatively low rates of insemination in recently established colonies, again often with documentation of improvement with increasing number of laboratory genera-229 extent to which laboratory conditions favour reproduction and survival of some genotypes over others ( ).…”
Section: Introductionmentioning
confidence: 98%